Reconciling Post-Exile Identities in Leila S. Chudori's novel "Pulang" - Anggreni Agustina Tamba; Rosmawaty Harahap (Journal of Aceh Studies, 2024)
Leila S. Chudori's novel Pulang recounts the characters' experiences reconciling their identities after returning from political exile abroad. This research aims to analyze the process of post-exile identity reconciliation experienced by the characters in the novel. This research employs a narrative analysis method, incorporating a postcolonial study approach. Data were obtained from the text of the Pulang novel and analyzed qualitatively. The results show that the process of reconciling the post-exilic identity experienced by the characters in the novel Pulang includes three main aspects: (1) acceptance of the dual identity formed during exile, (2) negotiation of local and global identities, and (3) efforts to rediscover cultural roots and personal history. The post-exile identity reconciliation process depicted in Pulang reflects the complexity of individuals' experiences and inner struggles during political exile. We expect the results of this study to offer fresh perspectives on identity dynamics and the effects of political exile within the framework of post-New Order Indonesian society. The findings can also contribute to a broader discussion on the impact of historical events on the formation of individual and collective identities.